Long-Term Treatment Outcomes of Micropulse Transscleral Cyclophotocoagulation in Primary and Secondary Glaucoma: A 5-Year Analysis - Ronald M. P. C. de Crom; Stefani Kujovic-Aleksov; Carroll A. B. Webers; Tos T. J. M. Berendschot; Henny J. M. Beckers (Ophthalmology and Therapy)
Abstract Introduction To investigate 5-year outcomes on intraocular pressure (IOP) and safety of micropulse transscleral cyclophotocoagulation (TSCPC) in patients with glaucoma. Methods Patients with mild to advanced glaucoma who underwent a standardized micropulse TSCPC procedure at the University Eye Clinic Maastricht from November 2016 to February 2019 were included. Results A total of 165 eyes were included, with outcomes for 112 eyes available after 5-year follow-up. Mean age was 67.3 ± 13.9 years; 58.2% were male. Glaucoma subtypes were primary glaucoma (n = 108) and secondary glaucoma (n = 57). Prior glaucoma surgery was performed in 65 of 165 eyes (39.4%). In the primary glaucoma group, mean preoperative IOP was 20.7 ± 7.1 mmHg. Mean postoperative IOP at 1, 2, 3, 4, and 5 years significantly reduced to 15.2 ± 6.5, 14.3 ± 5.0, 14.0 ± 4.9, 13.5 ± 4.1, and 12.9 ± 4.3 mmHg, respectively. Preoperatively, the mean number of IOP-lowering medications was 3.3 ± 1.3, which changed to 2.8 ± 1.3, 2.8 ± 1.2, 2.8 ± 1.2, 2.9 ± 1.2, and 2.7 ± 1.3 at 1, 2, 3, 4, and 5 years, respectively. In the secondary glaucoma group, mean preoperative IOP was 28.7 ± 10.3 mmHg, dropping significantly to 19.3 ± 10.4, 18.6 ± 11.3, 17.8 ± 9.8, 18.1 ± 12.0, and 15.5 ± 7.6 mmHg at the same intervals. The number of IOP-lowering medication was significantly reduced from 3.5 ± 1.1 to 2.5 ± 1.5, 2.2 ± 1.5, 2.6 ± 1.4, 2.6 ± 1.5, and 2.5 ± 1.7. In the total group, mean IOP reduction was 32.5% after 5 years. Postoperative complications included cystic macular edema (n = 3), fibrinous/uveitic reaction (n = 1), and rejection of corneal graft (n = 2), all reversible after treatment. One patient developed late and persisting hypotony. Other adverse events were retinal venous occlusion (n = 1) and retinal vasculitis (n = 1), unrelated to the laser treatment. In patients with a preoperative Central Distance Visual Acuity (CDVA) > 0.05 on the Snellen chart, more than two lines of visual acuity (VA) loss were attributed to cataract (n = 10), retinal disease (n = 5), glaucoma progression (n = 3), corneal decompensation (n = 2), or other factors (n = 11). Conclusion Micropulse TSCPC is a safe and effective treatment for reducing IOP and the number of IOP-lowering medications after a 5-year follow-up period. It is a viable alternative for patients after failed incisional glaucoma surgery or high-risk patients.